The Prevalence of Exit Gunshot Wound Shapes and the Relationship of the Shape to the Location of Exit Wounds - Pipatchotitham, Tossanai; Tangsermkijsakul, Aphinan (Asian Medical Journal and Alternative Medicine, 2022)
Objective: To study the prevalence of exit gunshot wound shapes and the relationships of exit gunshot wound shapes with sex, shooting distances, and sites of exit wounds. Design: Retrospective cross-sectional study Methods: Seventy-five autopsy reports of handgun death from 2010 to 2020 were retrospectively reviewed. There were 151 entrance wounds, 52 non-penetrating bullets, and one graze wound, leaving 98 complete wounds in the study. The following parameters were recorded from the files: sex, age, number of bullet tracks, sites of entrance wounds, shooting distance, bone perforation, sites of exit wounds, and shapes of the exit wounds. The primary outcome was exit gunshot wound shapes (circular, slit-like, crescent, stellate, and irregular). Prevalence of the shapes of exit gunshot wounds were recorded, and multinomial logistic regression analysis of the shape of exit wound, sex, shooting distance, bone perforation, and site of the exit wound was performed. Results: The most common shape of the exit gunshot wounds was circular wound with 31 cases (31.6%), followed by stellate, irregular, slit-like and crescent wound (27 cases (27.6%), 24 cases (24.5%), 12 cases (12.2%), 4 cases (4.1%)), respectively. The sex factor and the shooting distance did not affect the exit wound shape. Head exit location increased the likelihood of stellate wound formation compared to circular wound (adjusted odd ratio = 177.91, [95% CI 10.85 to 2,916.05], P-value < .001). Head exit location increased the likelihood of irregular shaped wounds compared to circular wound (adjusted odd ratio = 17.65, [95% CI, 1.54 to 201.84], P-value = .021). Bone perforation increased the likelihood of irregular shaped wounds compared to circular wound (adjusted odd ratio = 6.09, [95% CI, 1.54 to 24.10], P-value = .021) Conclusions: Exit gunshot wounds to the head are more likely to be stellate and irregular in shape. A stellate-shape wound can be an entrance or exit wound of the head and should be interpreted carefully.